(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Goods and Services Tax (GST) is a comprehensive tax system that would incorporate nearly all indirect taxes levied by state and federal governments. Even though many nations in the world still viewed it as the highest tax many years ago, India started to become active in the year 2000. The NDA government then established an empowered committee to create the model for the Goods and Services Tax (GST) and since then, numerous discussions have arisen regarding the implementation of GST in India. Ultimately, the Indian government promised to implement the GST by almost July 2017. We anticipate that the proposed GST will significantly alter the current indirect tax policy landscape.